Leader–member exchange and organizational commitment improve social business performance through organizational citizenship behavior - Asfiah, Nurul; Irawati, Sandra; Nurhasanah, Siti; Hakim, Arif Rahman (Jurnal Fokus Manajemen Bisnis, 2025)
Across diverse economies, social enterprises have emerged as key drivers of sustainable development, adopting innovative business models to address social and economic challenges. As the importance of social business performance continues to grow, understanding the organizational factors that enhance such performance is essential. This study investigates the influence of leader–member exchange and organizational commitment on social business performance, with organizational citizenship behavior as a mediating variable. The research was conducted among micro, small, and medium enterprises supported by the Aisyiyah network in East Java, Indonesia, involving 146 respondents. Data were analyzed using structural equation modeling with partial least squares. The results reveal that leader–member exchange significantly affects social business performance, whereas organizational commitment shows a negative and non-significant effect, indicating that the hypothesized positive relationship is unsupported. leader–member exchange also positively affects organizational citizenship behavior, while organizational commitment does not. Furthermore, organizational citizenship behavior significantly enhances social business performance and mediates the relationship between leader–member exchange and social business performance, but does not mediate the organizational commitment–social business performance link. These findings suggest leadership quality is more decisive than employee commitment in eliciting discretionary behaviors that improve social business outcomes. The study strengthens the relevance of social exchange theory in explaining leadership–behavior–performance dynamics in social enterprises. From a practical perspective, leaders and owners of social MSMEs should prioritize cultivating trust-based relationships and fostering organizational citizenship behavior through recognition systems, while aligning employee commitment with proactive contributions. Such strategies are vital for balancing financial sustainability with social value creation in emerging economies.